AN ANALYSIS OF QIRA’AH INSTRUCTION IN THE DIGITAL AGE TO ENHANCE UNDERSTANDING OF QUR’ANIC TEXTS AMONG SECOND-SEMESTER ARABIC LANGUAGE EDUCATION STUDENTS AT UIN RADEN INTAN LAMPUNG - Roliyah Noviyanti; Muhammad Nasiruddin; Ahmad Nur Mizan (LP2M IAI Al-Khairat Pamekasan, 2026)
This research is motivated by the low ability of students to understand the text of the Qur'an despite having the ability to read Arabic. In the digital era, Arabic language learning has developed through the use of various technological media that can support the learning process of qira'ah. This study aims to analyze the implementation of qira'ah learning in the digital era and its contribution to improving the understanding of the text of the Qur'an among Arabic Language Education students at Raden Intan State Islamic University, Lampung. This study uses a qualitative approach with a case study type. The research subjects consisted of 20 students and 1 lecturer teaching the qira'ah course. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results show that qira'ah learning in the digital era has utilized various media such as YouTube, Google Classroom, and digital dictionary applications. The use of digital media can increase student motivation and engagement in learning and help understanding the comprehension and structure of the text. However, there are still obstacles such as limited digital literacy and difficulties in understanding the meaning of the text in depth. Thus, digital-based qira'ah learning has the potential to improve understanding of the Quranic text, but requires more effective learning development strategies to achieve optimal results.